The laws of subtraction [ six simple rules for winning in the age of excess everything - May, Matthew E. (McGraw-Hill, 2013)
"6 simple principles for winning in an age of excess everythingMarket leaders know that success today depends upon the ability to create social value and personal engagement through the removal from offerings of anything deemed excessive, wasteful, unnecessary, unnatural, hard-to-use, or ugly. The Laws of Subtraction shows how the world's most original innovators stand out in a world of overwhelming choice and feature overload by employing subtraction and minimalism to create the most effective and engaging consumer experiences.Matthew E. May is the author of three award-winning books: The Shibumi Strategy, In Pursuit of Elegance, and The Elegant Solution. A popular speaker, creativity coach, and innovation advisor, he is a regular contributor to the American Express OPEN Forum Idea Hub and the founder of Edit Innovation, an ideas agency based in Los Angeles"